2017
DOI: 10.1111/jth.13768
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical safety and efficacy of andexanet alfa in animal models

Abstract: Essentials There is currently no approved reversal agent for factor Xa (FXa) inhibitors Andexanet alfa has been developed to reverse the anticoagulant effects of FXa inhibitors Andexanet reduced blood loss and anticoagulation markers in rivaroxaban-anticoagulated rabbits Andexanet was well tolerated in monkeys and rats, with no evidence of prothrombotic activity SUMMARY: Background Andexanet alfa is a recombinant modified form of factor Xa (FXa), designed to bind to and reverse the anticoagulant activity of FX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 19 publications
0
23
0
2
Order By: Relevance
“…26 These observations suggest that the elevations in these markers may reflect the hemostasis of endogenous coagulation and fibrinolytic activities and may not necessarily be associated with the development of thrombotic events. In support of the hypothesis that binding of andexanet to TFPI does not present a major safety concern, there was no evidence of thrombotic events attributed to andexanet in the preclinical toxicology studies in monkeys 18 or in clinical phase 3 studies in healthy volunteers. 19 The design and results of the phase 2 study reported here informed the design of the phase 3 studies that evaluated the ability of andexanet to reverse apixaban and rivaroxaban anticoagulation in older healthy subjects.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…26 These observations suggest that the elevations in these markers may reflect the hemostasis of endogenous coagulation and fibrinolytic activities and may not necessarily be associated with the development of thrombotic events. In support of the hypothesis that binding of andexanet to TFPI does not present a major safety concern, there was no evidence of thrombotic events attributed to andexanet in the preclinical toxicology studies in monkeys 18 or in clinical phase 3 studies in healthy volunteers. 19 The design and results of the phase 2 study reported here informed the design of the phase 3 studies that evaluated the ability of andexanet to reverse apixaban and rivaroxaban anticoagulation in older healthy subjects.…”
Section: Discussionmentioning
confidence: 61%
“…17 In animals treated with rivaroxaban, andexanet reversed its effects on plasma anti-FXa activity and reduced unbound rivaroxaban concentrations. 18 Furthermore, andexanet dose-dependently reduced bleeding in animals treated with enoxaparin or fondaparinux. 17 Here, we report original data from the phase 1 and 2 studies of andexanet administered to healthy volunteers, with or without apixaban anticoagulation.…”
Section: Introductionmentioning
confidence: 94%
“…In monkeys, they found neither significant safety concerns or unexpected outcomes. All observations were transient or reversible and included transient hypoactivity, labored respiration, vomiting, and anaphylactic reaction (Lu et al, 2017). Similarly to other antidotes, we tested the toxicity of HBC administered without heparin.…”
Section: Discussionmentioning
confidence: 99%
“…The development programs for both drugs had extensive preclinical programs in animals and cohorts of nonbleeding human beings. [2][3][4][5] The approval pathways were discussed with the Food and Drug Administration and thought leaders at the White Oak campus at the same meeting in 2014, the results of which were published. 6 Both trials, ReverseAD and ANNEXA-4, were launched shortly thereafter.…”
Section: Andexanet Responsementioning
confidence: 99%
“…"Structural violence is one way of describing social arrangements that put individuals and populations in harm's way," said Paul Farmer. 3 I suggest that we are dealing with a "structural" problem in drug development.…”
Section: Andexanet Responsementioning
confidence: 99%